Do we still need teachers? Navigating the paradigm shift of the teacher's role in the AI era - Gentile, Manuel; Città, Giuseppe; Perna, Salvatore; Allegra, Mario (Frontiers in Education, 2023)
Through a systematic analysis of the literature, this study analyzes the change in the teacher's role triggered by the integration of AI into educational systems. The picture offered by the systematic analysis of the literature conducted in this study reveals a less than total awareness of the urgency with which the challenges imposed by AI in the educational field must be addressed. We propose a manifesto to guide the evolution of the teachers' role according to the paradigm shift concept proposed by Kuhn in the scientific field.